Case Study : Fashionvalet Sdn.Bhd / Nur Alya Tasneem Baharom - Baharom, Nur Alya Tasneem (2021)
FashionValet Sdn.Bhd has been recognized by all Malaysian people and others countries. This is because of the multi-label online site stocking over 400 fashion designer and brands from South East Asia. Services and products that were offered by this store was shoes, makeup, bags, scarves, accessories and so on.